Kelekak Agroforestry in Central Bangka, Indonesia: Species Diversity, Challenges, and Conservation Strategies - Al Manar, Primadhika; Zuhud, Ervizal Amir Muhammad; Hikmat, Agus; Hidayat, Syamsul; Robika; Meilanto; Wilyan, Radil; Munggaran, Ikram Kurnia (Jurnal Sylva Lestari, 2025)
Forest land conversion has caused global climate change, reducing biodiversity and food security challenges. Climate change’s influence on food security must be anticipated promptly by adopting an adaptable agricultural cultivation system, such as agroforestry. The Bangka community is one of many that continue to practice agroforestry. In the Bangka community, agroforestry is known as kelekak. This research aims to learn about the history, variety of species, challenges, and conservation strategies of kelekak. This study's data was gathered through interviews, field observations, and literature studies. Kelekak is a woodland region historically used by the community to produce dryland rice (ume), which later became kelekak agroforestry land. Several fruit plant species are commonly found on kelekak land, including durian (Durio zibethinus), mangosteen (Garcinia mangostana), cempedak (Artocarpus integer), and ketapi (Sandoricum koetjape). The community utilizes various plant species in the kelekak as food, medicine, building materials, and firewood. Kelekak’s survival is threatened by land conversion to monoculture plantations, limiting community resource access. Efforts to revive the kelekak can be achieved through the Tri Stimulus Amar Pro-Konservasi approach by integrating natural, benefit, and religious willingness stimulus. Efforts to reinvigorate kelekak must begin immediately, with mapping activities for the remaining kelekak in the Central Bangka area to provide primary data for future kelekak development and local government regulations to conserve kelekak. Keywords: agroforestry, conservation, food, forest, kelekak